The Effectiveness of Using LiveWorksheets on Students’ Reading Skill of Narrative Text at MAN Temanggung - Husain Subroto, Fatimatu Khoirunnisa; Arochman, Taufik; Karma, Carolus Prima Ferri (EduLine: Journal of Education and Learning Innovation, 2024)
This study aimed to determine whether there is a significant difference in reading skills between students taught using LiveWorksheets and those taught with paper-based worksheets, as well as to understand students' perceptions of using LiveWorksheets to improve their reading skills. The research was quasi-experimental and involved tenth-grade students at MAN Temanggung, selected through purposive sampling into a control class and an experimental class, each with 36 students. Data were collected through tests (pretest and posttest) and questionnaires. Test data were analyzed using SPSS, while non-test data were analyzed using descriptive quantitative methods. The data analysis reveals a significant difference in reading skill scores between students taught with LiveWorksheets and those taught with paper-based worksheets, with a significance value of 0.032, indicating the difference is statistically significant. Students' perceptions of LiveWorksheets are very positive, with 90.73% rating its use in assessments highly and 93.05% recognizing its benefits in reading. Additionally, 88.88% of students strongly disagreed that LiveWorksheets have significant weaknesses, leading to an overall approval rating of 91.55%. The study concludes that LiveWorksheets is effective in improving students' narrative text reading skills, with most students viewing it as an effective and useful tool without notable drawbacks.